VARIASI MORFOMETRIK IKAN MUJAIR (Oreochromis mossambicus) PADA EKOSISTEM RAWA (LENTIK WATER) DI WILAYAH PRAFI, MASNI DAN SIDEY, KABUPATEN MANOKWARI - Sigit Prafiadi; Enik Maturahmah (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine the pattern of breeding, adaptability to the environment and feeding processes in tilapia fish Oreochromis mossambicus through morphological data, morphological data obtained through morphometric measurements that can be used to formulate the extent of the threat to local species because tilapia is an invasive fish species with morphological data. Fairly high reproduction in freshwater waters. The location of this research is swamp waters in Manokwari Regency, namely Prafi, Masni and Sidey Regions. Morphometric measurements using 14 standards. Morphometric measurement results of male fish showed that the width of the tail fin (CFW) there was a significant difference in the width of the tail fin (CFL) between the tilapia fish in the Prafi swamp with the other two marshes, the width of the tilapia fish tail fins in the Masni and Sidey swamps did not differ significantly. In female fish measurements (DFL) showed that there were significant differences while the CFW measurements contained in the Prafi swamp were different from the other two marshes. The results of the morphometric measurements show how the morphological characteristics of tilapia fish will have an impact on local fish and the amount of natural food in the Swamp.